2010
DOI: 10.1186/cc9328
|View full text |Cite
|
Sign up to set email alerts
|

Procalcitonin reflects bacteremia and bacterial load in urosepsis syndrome: a prospective observational study

Abstract: IntroductionGuidelines recommend that two blood cultures be performed in patients with febrile urinary tract infection (UTI), to detect bacteremia and help diagnose urosepsis. The usefulness and cost-effectiveness of this practice have been criticized. This study aimed to evaluate clinical characteristics and the biomarker procalcitonin (PCT) as an aid in predicting bacteremia.MethodsA prospective observational multicenter cohort study included consecutive adults with febrile UTI in 35 primary care units and 8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
105
3
30

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 168 publications
(147 citation statements)
references
References 36 publications
9
105
3
30
Order By: Relevance
“…Although sepsis was a concern from the date of presentation, the degree of PCT elevation in this patient may suggest another etiology. PCT levels reported in the literature of patients with urinary tract infections report maximum PCT levels far lower than those observed in our patient, for example Van Nieuwkoop et al, reported a maximum of 9.07 ug/L [4] . In our patient, the PCT was observed to dramatically increase after cardiac arrest and recurrent external defibrillations and thus seemed correlative.…”
Section: Discussioncontrasting
confidence: 81%
“…Although sepsis was a concern from the date of presentation, the degree of PCT elevation in this patient may suggest another etiology. PCT levels reported in the literature of patients with urinary tract infections report maximum PCT levels far lower than those observed in our patient, for example Van Nieuwkoop et al, reported a maximum of 9.07 ug/L [4] . In our patient, the PCT was observed to dramatically increase after cardiac arrest and recurrent external defibrillations and thus seemed correlative.…”
Section: Discussioncontrasting
confidence: 81%
“…13 As to other inflammation marker, some studies show that serum procalcitonin has a role in more accurate prediction of bacterial infection 14 and bacteremia with febrile UTI 15 than CRP and WBC count. Our data showed significantly more cases of shock with urinary tract occlusion that required stenting.…”
Section: E107mentioning
confidence: 99%
“…A level >0.25 ug/L predicted bacteremia, and for bacteremic subjects procalcitonin level correlated with bacterial load measured as time to positive culture [32]. Of 136 bacteremic patients, 29 (21%) had urine cultures which were negative, contaminated, or grew an organism different from that isolated from the blood [33].…”
Section: Complicated Urinary Tract Infectionmentioning
confidence: 99%